Lophiaris tapiae, a new species of the Lophiaris oerstedii complex (Orchidaceae) from the Yucatan Peninsula, Mexico - Balam, Ricardo; Carnevali, Germán; Cetzal-Ix, William; Duno, Rodrigo (Instituto de Ecología, A.C., 2011)
Lophiaris tapiae Balam & Carnevali (Orchidaceae: Oncidiinae) is described and illustrated. The new species is known only from the Escarcega area, and the Candelaria and Palizada rivers margins in the state of Campeche, Mexico. It is compared with species of the Lophiaris oerstedii complex, particularly with L. andrewsiae, to which it is closely related. A distribution map for the species and an identification key for all taxa of the L. oerstedii complex are included. We propose an “in danger of extinction” (P) conservation status for L. tapiae when assessed against the Method for Evaluation of Risk of Extinction for Mexican Wild Species (MER) criteria.